How the Supply Chain Management Practices influence on Operational Performance? A Case of Manufacturing Firms in Sri Lanka - H.M.P.P.S. Herath; D.M. Endagamage (Integrated Journal for Research in Arts and Humanities, 2022)
Most organisations in different sectors are implementing Supply Chain Management Practices (SCMPs) to create faster, more effective, and cost-beneficial relationships between business partners, to increase their Operational Performances. Even though the firms use SCMPs, their knowledge regarding the effectiveness of these practices is questionable. The aim of this study was to identify the most influential SCMPs on the Operational Performances of the Sri Lankan manufacturing industry. As to the literature and due to the high level of applicability in the manufacturing sector, five factors; Supply Relationship Management, Customer Relationship Management, Information Sharing, Logistics, and Outsourcing of Services were selected to conceptualize the current study. The Operational Performance of a Manufacturing organization has defined as the performance related to the quality, cost, delivery, and flexibility to change the volume. This was a cross-sectional questionnaire based survey which is quantitative in nature and primarily concerned with the testing of hypotheses. A set of 37 close-ended questions used to collect data from 200 randomly selected organizations. However, due to the difficulties faced in the pandemic environment, the success rate was 58.5%. Results of the Correlation Analysis confirmed the relationships hypothesized according to the theoretical behaviour with positive relationships significant at a 1% level. The strongest relationship shows between Logistics and Operational Performances (0.832). Regression Analysis showed significant impacts of Supplier Relationship Management (β=0.276) and Logistics (β=0.261) on the Operational Performance. Customer Relationship Management, Information Sharing, and outsourcing were not showed a significant impact on the Operational Performance at the 5% level. The adequacy of the fitted model is 67% and the RMSE is 0.236. The residual analysis also ensured the accuracy of the model with normally distributed residuals, free of Multi-collinearity, and having homoscedasticity which emphasises the constant variance of the residuals. The findings emphasise that if the SCMPs is running at a righteous level, an organization can keep their Operational Performances at a higher level. However, only the Supplier Relationship and Logistic activities are the factors significantly influencing the Operational Performances of the Manufacturing sector in Sri Lanka. Similar to the facts highlighted in the literature, the responses of the current study also showed a poor level of handling and utilizing customer feedback for the development of Sri Lankan organizations. Information sharing also showed a poor focus on integrating and enhancing the IT systems. The uncontrollable circumstances due to outsourcing the services lead to a poor level of operational performance at the finale. This research contributes to the existing Supply Chain Management literature by providing empirical evidence from the Sri Lankan manufacturing industry.